2011
DOI: 10.1108/13555851111183057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived quality on brand equity: an empirical study on generic drugs

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 44 publications
0
35
0
15
Order By: Relevance
“…In order to maximize the long-term performance of an organization, marketing managers require pursuing a more accountable marketing investment by continuous monitoring of equity (Ramaseshan, Rabbanee, & Hui, 2013). Hutchinson et al (2009) and Sanyal and Datta (2011) have found that perceived quality has a positive influence on perceived equity. On the other hand, Budiarti et al (2013) indicate that perceived equity plays a critical role in increasing satisfaction.…”
Section: Equitymentioning
confidence: 99%
“…In order to maximize the long-term performance of an organization, marketing managers require pursuing a more accountable marketing investment by continuous monitoring of equity (Ramaseshan, Rabbanee, & Hui, 2013). Hutchinson et al (2009) and Sanyal and Datta (2011) have found that perceived quality has a positive influence on perceived equity. On the other hand, Budiarti et al (2013) indicate that perceived equity plays a critical role in increasing satisfaction.…”
Section: Equitymentioning
confidence: 99%
“…The objective characteristics of a product include intrinsic as well as extrinsic signals of quality. Intrinsic signals lead to perceived quality and the perceived quality, increase the brand equity so managers should strive to reduce the gap between the expected perceived qualities and observed perceived quality (Sanyal & Datta, 2011).…”
Section: Perceived Quality and Brand Loyaltymentioning
confidence: 99%
“…First, although more than 15 years passed over the case of "generic scandal" caused by FDA reviewers' accepting bribes from generic drug manufacturers for the approval of ANDAs, and violating manufacturing procedures and using fabricated supported documents for application, there is still a prejudice against the quality of generic drugs which impairs the reputation of generic drug manufacturers worldwide [24]. The second is the view that in certain circumstances generic substitution is not always appropriate [25]. The approval of generic drug requires showing its biological equivalence (bioequivalence) to the reference (original) drug.…”
Section: Discussionmentioning
confidence: 99%